Flail chest due to blunt trauma: clinical features and factors affecting prognosis - Balci, Akin E.raslan; Ozalp, Koray; Duran, Mehmet; Ayan, Erhan; Vuraloğlu, Sadik (My University, 2004)
[Abstract Not Available]
Künt travmaya bağli yelken göğüs: Klinik özellikler ve prognozu etkileyen faktörler
Keywords: Accidents, Traffic; Adolescent; Adult; Female; Flail Chest; Humans; Lung Injury; Male; Middle Aged; Prognosis; Retrospective Studies; Rib Fractures; Wounds, Nonpenetrating; Young Adult; adolescent; adult; complication; female; flail chest; human; lung injury; male; middle aged; pathophysiology; prognosis; retrospective study; rib fracture; traffic accident; Wounds, Nonpenetrating; young adult